PENGARUH IKATAN HUBUNGAN, CITRA PERUSAHAAN, NILAI PELANGGAN, KUALITAS DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH BANK PEMERINTAH DI JAWA TENGAH - Naili Farida (Sekolah Pascasarjana Universitas Brawijaya, 2010)
Abstract The study discusses about the integration of relational bonding, relational quality, customer satisfaction, and customer loyalty at the state-owned bank in Central Java. The locations of research include Semarang City, Surakarta City, and Cilacap City. Research method uses multi stage sampling. The sample of research counts to 278 customers of Regular Saving from Bank Negara Indonesia (BNI), Bank Mandiri, Bank Rakyat Indonesia, Bank Tabungan Negara, and Bank Pembangunan Jateng. The hypothesis test in this research employs descriptive analysis and Structural Equation Modeling (SEM). The descriptive analysis has loading factor and 5 % significance rate. The objective of research will be to understand and to analyze the relational bonding between the Bank customers through corporate image, customer value, and relational quality as well as customer satisfaction on customer loyalty. The state-owned banks in Central Java already use this model. Result of research in relative with the result of SEM analysis indicates that the relevancy of relational bonding, corporate image, customer value, and customer satisfaction has significant effect on customer loyalty. Therefore, this model should be developed by the state-owned banks to increase the customer loyalty. Keywords: Relational bonding, Corporate image, Customer value, Relational quality, Service quality, Customer loyalty